The Theory and Practice of Language Faculty Science - Hajime Hoji; Daniel Plesniak; Yukinori Takubo (De Gruyter Mouton, 2022)
The book demonstrates that it is possible to study the language faculty with the core scientific method, i.e., by deducing definite predictions from hypotheses and obtaining and replicating experimental results precisely in accordance with the predictions.In light of the'reproducibility crisis'as extensively addressed in recent years in a number of fields, the demonstration that rigorous replication can be obtained in the study of the language faculty in terms of correlational and categorical predictions is particularly significant. While the claim has been made over the years that Chomsky's research program is meant to be a scientific study of the language faculty, a conceptual and methodological articulation has never been made as to how we can accumulate our knowledge about the language faculty by the basic scientific method, including, most crucially, how exactly we can put our hypotheses to rigorous empirical and experimental test.The book proposes how to do that by providing a conceptual basis for the methodology for language faculty science. The book also offers empirical demonstrations of the viability of the proposed methodology. The experiments were conducted with Japanese and English speakers. Overall, the book explores new directions for the study of the mind.